2017
DOI: 10.1111/aos.13559
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐instillation of fluorescein with an inoculation loop for ocular surface staining in dry eye syndrome

Abstract: The 1 μl-calibrated inoculation loop is a safe, convenient, inexpensive, disposable, sterile, well-tolerated tool for reproducible micro-instillation of commercial fluorescein. By greatly improving staining quality, it will help standardize assessment of dry eye severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…There are several accepted methods for delivering uorescein sodium solution onto the ocular surface when performing uorescein staining. [5] In the current study, we compared standard uorescein strips and a 1 mL syringe method with an innovative newly developed uorescein pen. The standard uorescein strip method cannot administer exact concentrations and quantities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several accepted methods for delivering uorescein sodium solution onto the ocular surface when performing uorescein staining. [5] In the current study, we compared standard uorescein strips and a 1 mL syringe method with an innovative newly developed uorescein pen. The standard uorescein strip method cannot administer exact concentrations and quantities.…”
Section: Discussionmentioning
confidence: 99%
“…The reported concentrations of uorescein used in ocular surface staining differ, ranging from 0.1-1% [5][6][7]. We applied a concentration of 0.5% in our study, because this was the optimal concentration identi ed in our pilot study and because we use this concentration for corneal staining in our practice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Raj et al 49 also found a positive correlation between Schirmer's and tear meniscus and concluded that OCT enables a better understanding and treatment of DED. Tear meniscus height measurements obtained by frequency domain OCT and a keratograph were compared by Baek et al 50 and Arriola et al 51 52 presented an all-in-one non-contact ocular surface imaging device (LacryDiag-Quantel Medical) that measures various dry eye parameters that include the tear meniscus height. It also provides lipid layer analysis, non-invasive breakup time (NIBUT), and meibography analysis, which all require manual intervention to obtain the final quantification.…”
Section: Semi-automated Methodsmentioning
confidence: 99%
“…Courrier et al 52 presented an all‐in‐one non‐contact ocular surface imaging device (LacryDiag‐Quantel Medical) that measures various dry eye parameters that include the tear meniscus height. It also provides lipid layer analysis, non‐invasive breakup time (NIBUT), and meibography analysis, which all require manual intervention to obtain the final quantification.…”
Section: Tear Secretion and Volumementioning
confidence: 99%
“…In addition, an additional donor cornea was infected in the ASM with the same protocol and observed with an ophthalmologic slit lamp after fluorescein staining [26] (Fluorescein Faure single dose, SERB Laboratories, Paris, France) to show clinician readers the similarity in pattern to dendritic keratitis in vivo.…”
Section: Hsv-1 Infection Of Human Corneal Tissue Ex Vivomentioning
confidence: 99%